Friendship Learning: Model Pembelajaran Berbasis Nilai-Nilai Pluralisme Islam - Salim, Bairus (JOIES (Journal of Islamic Education Studies), 2017)
Islam recognizes the diversity (pluralism). The reality of diversity requires humans to know each other, help one another and appreciate one another. In the context of education and learning, the values of pluralism can be the inspiration for the birth of a learning model called the Frienship Learning. So called, because chronologically values recognize each other, help one another, and appreciate forming a system of friendship. Viewed from the aspect of learning theory, friendship learning builds scientific structures scientifically but is thick with the nuances of social interaction so that it can be called social constructivism. Operationally, the friendship learning model has stages of exploration, collaboration and appreciation. Its implementation in learning through a student centered approach (learner centered), inductive strategies and using methods of Islamic education.